DRES-02. CILIARY PROTEIN ARL13B PROMOTES CHEMORESISTANCE BY MODULATE GLIOBLASTOMA PURINE BIOSYNTHESIS. (5th November 2018) - Shireman, Jack; Atashi, Fatemeh; Park, Cheol; Warnke, Louisa; Miska, Jason; Ahmed, Atique
Abstract: Glioblastoma (GBM) carries with it an almost 100% recurrence rate due to development of resistance to all conventional therapies. Our lab has demonstrated ARL13B, an ADP-ribosylation factor-like protein critical for cilia formation, plays an important role in promoting resistance to temozolomide (TMZ)-based chemotherapy. Knockdown of ARL13B in patient derived xenograft cells significantly increased survival of mice in an orthotropic GBM model when compared to controls (p<0.0001).The Cancer Genome Atlas (TCGA) dataset demonstrates time to recurrence in patients with downregulated ARL13B is substantially increased as compared to ARL13B upregulated patients (log-rank p-value=0.0012).To better understand the role of ARL13B in therapeutic adaptation we performed mass spectrometry analysis of an ARL13B pulldown during TMZ therapy and identified inosine monophosphate dehydrogenase 2 (IMPDH2), the rate-limiting enzyme in de-novo guanine nucleotide biosynthesis, as a significant binding partner of ARL13B during TMZ chemotherapy (p<0.0001). Immunoprecipitation analysis across multiple GBM cell lines validated this interaction and its increase during TMZ therapy. Probing this interaction further we examined the de novo and salvage purine biosynthesis pathways using radiolabeled carbon tracing experiments. In ARL13B knockdown cells, purine salvage pathway usage is upregulated 7-fold (p<0.0001) while de-novo pathway usage was decreased about 50% (p=0.004) in a TMZ specific manner. Moreover, ARL13B knockdown GBM cells treated with TMZ show a robust increase in DNA double-strand breaks compared to control cells exposed to TMZ, demonstrated by γH2X staining. Based on these observations, we hypothesize that ARL13B is a novel regulator of IMPDH2 allowing GBM cells to block salvage pathway biosynthesis to avoid TMZ induced DNA damage. However, when ARL13B is lost, GBM cells are forced into salvage pathway synthesis thus becoming sensitized to TMZ therapy due to increased incorporation of alkylated purines, a known function of TMZ.